Market study for a production unit of natural flavours for yoghurts: Part 2. Operational challenges and financial profitability analysis - Orounladji, Boko Michel; Tankoano, Abel; Sib, Ollo; Vall, Eric (2024)
The aim of this market study was to determine the feasibility and potential of setting up an extract production unit based on local products (PNFL and various agricultural products) to flavour yoghurts made from local milk in the Bobo-Dioulasso dairy basin. More specifically, the project involved  Analyse of milk processor demand on yogourts  Identify consumer preferences and expectations  Assess the technical and logistical challenges  Analyse market opportunities and financial profitability This report, which follows on from the first part of the study devoted to analysing processor demand and identifying consumer preferences and expectations (Orounladji et al., 2024), presents the results of the study relating to the last two points listed above.